ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PEMERINTAH DAERAH (STUDI KASUS LAPORAN HASIL PEMERIKSAAN BPK ATAS LKPD KABUPATEN ACEH TIMUR KHUSUS PADA LAPORAN REALISASI ANGGARAN) - Saputra, Ryanda; Putri, Desyana (Universitas Dharmawangsa, 2024)
This research aims to examine the financial performance of the local government Aceh Timur Regency. This analysis uses regional financial independence ratios, financial efficiency ratios, PAD effectiveness ratios, and the ratio of harmoni to assess financial performance. This study is included in the category of quantitative descriptive research. The data used comes from the Financial Report of the local government Aceh Timur Regency for the 2019-2023 budget period. Financial ratio analysis is the method used to perform this analysis. As shown by the research results, the financial performance of the Aceh Timur Regency Government is still far from optimal. Regional Original Revenue Management is still not successful, and regional finances are still inefficient. In addition, the level of regional independence is still low, as shown by the increase in central government assistance compared to the regional original income of Aceh Timur Regency.